Geographical distribution of diabetes patients in the Kingdom of Saudi Arabia (2019) with a global overview of diabetes prevalence - Al-Qahtani, Ayedh Abdullah (Journal of Humanities & Social Sciences, 2025)
This study aims to know the geographical distribution of diabetes patients in the Kingdom of Saudi Arabia, know of the pattern of geographical distribution of diabetes clinics at the level of regions of the Kingdom of Saudi Arabia, in addition to identify the global geographical areas of diabetes, and the ten countries with the most diabetes in the world. The study found that the percentage of diabetes cases with type I and II, both diagnosed and undiagnosed in the Kingdom of Saudi Arabia for the year 2019 is estimated at (18.3%) of the total population of the Kingdom of Saudi Arabia and with an estimated number of (6.119,824) injured, and with a constant estimated at (183) cases in every thousands of the population of Saudi Arabia. The study also found that the region of Makkah Al-Mukaromah tops the regions of the Kingdom of Saudi Arabia in the number of people with diabetes, as well as the regions of the Kingdom in the percentage of Saudi and non-Saudi patients for diabetes clinics. While the northern border region comes last of the regions of the Kingdom of Saudi Arabia in the number of people with diabetes. It was also clear from the study that the direct economic burdens resulting from diabetes in the Kingdom of Saudi Arabia are estimated at (7.2) billion riyals during 2019. The study recommends the necessity of creating a national policy aimed at implementing preventive programs and measures to reduce the spread of diabetes in the Kingdom of Saudi Arabia, as well as the need to conduct continuous media campaigns at the national level, to warn of this silent disease, and the need to place emphasis on monitoring the risk factors causing diabetes and controlling it Such as the increasing prevalence of obesity, and the marriage of relatives, in addition to a stable and a lifestyle far from making a dynamic sports effort, and finally the study recommends the establishment of research centers to study diabetes, support scientific research by all available means, and provide health data and statistics to researchers.